AESTHETIC VALUES AND EDUCATIONAL PHILOSOPHY IN TARI BARIS BABUANG IN BATULANTANG VILLAGE, PETANG DISTRICT, BADUNG REGENCY - I Gusti Ngurah Okta Diana Putra; I Wayan Budiarsa; I Gede Mawan; Ni Luh Desi In Diana Sari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Baris Babuang Dance is a sacred Balinese performing art tradition originating from Batulantang Village, Petang District, Badung Regency, Bali, which was officially recognized as an Indonesian Intangible Cultural Heritage in 2021. Beyond its function as a ritual performance, the dance embodies aesthetic values and educational philosophies that play an important role in cultural transmission and character formation within the local community. This study aims to analyze the aesthetic values of the Baris Babuang Dance through Djelantik’s aesthetic framework of form, content, and appearance; examine the educational philosophy embedded in its performance and transmission processes; and explore its relevance to the development of local wisdom-based arts education. The research employed a qualitative ethnographic approach conducted in Batulantang Traditional Village. Data were collected through participant observation, semi-structured interviews, documentation, and literature review, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the aesthetic values of the Baris Babuang Dance are manifested through its dynamic choreographic structure, symbolic ritual properties, sacred performance context, and integration of artistic, spiritual, and cultural dimensions. The educational philosophy embodied in the dance encompasses values of discipline, responsibility, communal solidarity, spirituality, cultural stewardship, and character formation transmitted through participatory and intergenerational learning processes. Furthermore, the study demonstrates that the Baris Babuang Dance possesses significant relevance for local wisdom-based arts education by providing curricular, pedagogical, and cultural foundations for strengthening cultural identity and character education. The study concludes that the Baris Babuang Dance represents a living cultural heritage that functions simultaneously as a sacred artistic expression, a medium of cultural transmission, and a valuable educational resource for contemporary arts education.